La classe à plusieurs cours à l’épreuve du modèle de la classe homogène. Une organisation pédagogique subversive de la forme scolaire ? - Sylvie Jouan (Éducation et Socialisation)
Starting from the observation that nearly one pupil in two is nowadays enrolled in a multigrade class in France, this article highlights the hiatus between the frequency of this class configuration, historically anchored in the French school landscape since the 19th century in the initial form of the one class school, and the very low consideration of these classes on the part of the state school institution. After a presentation of the state of the art on the performance of French multigrade classes, an analysis of several institutional writings since the end of the 19th century allows us to corroborate the hypothesis that the reticence towards these classes can be explained by the attachment to a pedagogical model incompatible with the reality of a multigrade class: a model of simultaneous teaching, consubstantial with the school form, prescribing the constitution of homogeneous classes. The multigrade class, in particular the one that brings together more than two grades, thus appears as potentially subversive of this school form.